Emotional Geographies of Exclusion: Whiteness and Ability in Teacher Education Research. Issue 7 (July 2022) - Beneke, Margaret R.; Siuty, Molly Baustien; Handy, Tamara
Context: Geographies of exclusion (e.g., segregated special education classrooms, school district zoning) are constituted through intersecting oppressive ideologies (e.g., ableism, racism, classism) that co-naturalize notions of "normalcy" and deviance and yield harmful consequences for disabled children of Color. Geographies of exclusion dynamically contribute to and constitute teacher candidates' feelings about themselves and their social worlds. White teacher candidates' investment in dominant racial ideologies is well-documented, and recent scholarship has interrogated the role of white emotionality in these processes. However, the extent to which white teacher candidates emotionally ascribe to oppressive constructions of ability have been underexamined. Focus of Study: We sought to uncover how white teacher candidates (TCs) used emotional practices to position themselves in relation to ability within geographies of exclusion as they narrated their educational journeys. Such an examination is necessary to upend ongoing constructions of racial-ability hierarchies in and through teacher education. Using disability critical race theory and emotional geographies, our study was guided by the following question: How do white, nondisabled TCs engage in emotional practices in relation to geographies of exclusion? Research Design: This critical narrative study took place in two teacher education programs in the Pacific Northwest with 42 white, nondisabled teacher candidates. We drew on qualitative mapping as a method for participants to tell stories about themselves and their relationships to places and people over time. All participants generated narratives through written reflections after creating their maps, clarifying aspects of their maps and providing details not captured in their visual representations. Data sources included 42 written narratives and 36 qualitative maps. We analyzed emotional dimensions of TCs' written narratives and qualitative maps through multiple rounds of both deductive and inductive coding. Conclusions/Recommendations: Our analysis revealed ways white TCs weaponized emotionality to uphold racial-ability hierarchies through emotional geographies of gratitude, ambivalence, and claims to care. By sentimentalizing multiply-marginalized children's suffering, TCs preserved a façade of being committed to educational justice. We conclude with suggestions for educational researchers, emphasizing that research with white teachers cannot ignore emotional practices that perpetuate harm for multiply-marginalized children. Instead, researchers must surface these engagements head-on, using DisCrit as a driver in teacher education research toward intersectional justice.